Peroxisomal L-bifunctional Protein Deficiency Causes Male-specific Kidney Hypertrophy and Proximal Tubular Injury in Mice. Issue 9 (30th September 2021) - Ranea-Robles, Pablo; Portman, Kensey; Bender, Aaron; Lee, Kyung; He, John Cijiang; Mulholland, David J.; Argmann, Carmen; Houten, Sander M.
Visual Abstract: Abstract : Key Points: Deficiency of EHHADH, a peroxisomal β -oxidation enzyme, causes male-specific kidney hypertrophy and proximal tubular injury in mice. Our work suggests genetic defects in peroxisomal metabolism may be a cause of CKD. Our work also indicates that sexual dimorphism in tubular metabolic homeostasis affects susceptibility to kidney disease. Background: Proximal tubular (PT) cells are enriched in mitochondria and peroxisomes. Whereas mitochondrial fatty acid oxidation (FAO) plays an important role in kidney function by supporting the high-energy requirements of PT cells, the role of peroxisomal metabolism remains largely unknown. L-bifunctional protein (EHHADH) catalyzes the second and third step of peroxisomal FAO. Methods: We studied kidneys of WT and Ehhadh KO mice on a C57BL/6N background using histology, immunohistochemistry, immunofluorescence, immunoblot, RNA-sequencing, and metabolomics. To assess the role of androgens in the kidney phenotype of Ehhadh KO mice, mice underwent orchiectomy. Results: We observed male-specific kidney hypertrophy and glomerular filtration rate reduction in adult Ehhadh KO mice. Transcriptome analysis unveiled a gene expression signature similar to PT injury in AKI mouse models. This was further illustrated by the presence of kidney injury molecule-1 (KIM-1), SOX-9, and Ki67-positive cells in the PT of male Ehhadh KO kidneys. Male Ehhadh KO kidneys had metabolite changes consistent with peroxisomal dysfunction and an elevation in glycosphingolipid levels. Orchiectomy of Ehhadh KO mice decreased the number of KIM-1–positive cells to WT levels. We revealed a pronounced sexual dimorphism in the expression of peroxisomal FAO proteins in mouse kidney, underlining a role of androgens in the kidney phenotype of Ehhadh KO mice. Conclusions: Our data highlight the importance of EHHADH and peroxisomal metabolism in male kidney physiology, and reveal peroxisomal FAO as a sexual dimorphic metabolic pathway in mouse kidneys.